An electrospun scaffold functionalized with a ROS-scavenging hydrogel stimulates ocular wound healing. (1st March 2023) - Shi, Xin; Zhou, Tong; Huang, Shenyu; Yao, Yuejun; Xu, Peifang; Hu, Shaodan; Tu, Chenxi; Yin, Wei; Gao, Changyou; Ye, Juan
Abstracts: Ocular alkali burn is a serious ophthalmic emergency. Highly penetrative alkalis cause strong inflammatory responses leading to persistent epithelial defects, acute corneal perforation and severe scarring, and thereby persistent pain, loss of vision and cicatricial sequelae. Early and effective anti-inflammation management is vital in reducing the severity of injury. In this study, a double network biomaterial was prepared by compounding electrospinning nanofibres of thioketal-containing polyurethane (PUTK) with a reactive oxygen species (ROS)-scavenging hydrogel (RH) fabricated by crosslinking poly(poly(ethylene glycol) methyl ether methacrylate-co-glycidyl methacrylate) with thioketal diamine and 3, 3′-dithiobis(propionohydrazide). The developed PUTK/RH patch exhibited good transparency, high tensile strength and increased hydrophilicity. Most importantly, it demonstrated strong antioxidant activity against H2 O2 and 2, 2-di(4-tert-octylphenyl)-1-picryl-hydrazyl (DPPH). Next, a rat corneal alkali burn model was established, and the PUTK/RH patch was transplanted on the injured cornea. Reduced inflammatory cell infiltration was revealed by confocal microscopy, and lower expression levels of genes relative to inflammation, vascularization and scarring were identified by qRT-PCR and western blot. Fluorescein sodium dyeing, hematoxylin and eosin (H&E) staining and immunohistochemical staining confirmed that the PUTK/RH patch could accelerate corneal wound healing by inhibiting inflammation, promoting epithelial regeneration and decreasing scar formation. Statement of significance: Ocular alkali burn is a serious ophthalmic emergency, characterized with persistent inflammation and irreversible vision loss. Oxidative stress is the main pathological process at the acute inflammatory stage, during which combined use of glucocorticoids and amniotic membrane transplantation is the most widely accepted treatment. In this study, we fabricated a polyurethane electrospun nanofiber membrane functionalized with a ROS-scavenging hydrogel. This composite patch could be a promising amniotic membrane substitute, possessing with a transparent appearance, elasticity and anti-inflammation effect. It could be easily transplanted onto the alkali-burned corneas, resulting in a significant inhibition of stromal inflammation and accelerating the recovery of corneal transparency. The conception of ROS-scavenging wound patch may offer a new way for ocular alkali burn. Graphical abstract: Image, graphical abstract